Transparency and market quality: Evidence from SuperMontage - Chung, Kee H.; Chuwonganant, Chairat (Journal of Financial Intermediation, 2009)
In this study, we examine the effect of pre-trade transparency on market quality using data before and after the introduction of SuperMontage. Our results show that both bid–ask spreads and return volatility declined significantly after the implementation of SuperMontage. In addition, SuperMontage led to significant improvements in the SEC Rule 605 execution quality measures (e.g., faster executions and higher fill rates). Overall, our results indicate that SuperMontage improved market and execution quality on NASDAQ through greater pre-trade transparency and the integrated, more efficient quotation and trading system.